Passalidae (Coleoptera: Scarabaeoidea) from the West-Most Brazilian Amazon Region: Checklist, New Records, and Identification Key - Bevilaqua, Marcus Vinícius Oliveira; Fonseca, Claudio Ruy Vasconcelos da (Neotropical Entomology, 2019)
We present a list of Passalidae species found in the westmost Brazilian Amazon region, which is considered to be a diversity-rich area due to being a tectonic and geographic transition zone in relation to Brazilian Amazon lowlands and the Andean range. The specimens acquired in field collections and museums were analyzed. Their geographical distributions were estimated based on data from labeled specimens and the literature. Twenty-nine species belonging to two subfamilies, six genera, and four subgenera were listed. Among them, 20, 1, and 2 showed to be new records for the region, Brazilian Amazon, and Brazil, respectively. An identification key is provided for the species being listed. © 2018, Sociedade Entomológica do Brasil.
Keywords: Animals; Animals Dispersal; Beetle; Classification; Animals Distribution; Animal; Coleoptera